Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.18632/aging.203951
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-29a inhibits atherosclerotic plaque formation by mediating macrophage autophagy via PI3K/AKT/mTOR pathway

Abstract: Background: miR-29a plays a vital role in AS, but the relationship between the miR-29a-targeted PI3K signaling pathway and AS remains unclear. Therefore, this study was carried out. Methods: Gene expression profiles from the GEO database containing AS samples were analyzed. ApoE −/− mice and RAW264.7 cells were treated with miR-29a negative control (NC), miR-29a mimic and miR-29a inhibitor to establish the AS model. Then MOVAT staining, TEM, Western blotting, and immunofluorescence staining were adopted for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…The authors thought that these findings may be related to the different pathological conditions of the diseases. In the present work, miR‐29a‐3p was downregulated in LPS‐stimulated BV2 cells, and its restoration strikingly alleviated inflammatory responses and NLRP3 inflammasome by enhancing autophagy, which was similar to Shao et al's report 29 . Moreover, bioinformatics software analysis and literature showed that miR‐29a‐3p was related to CpG‐mediated DNA methylation 32 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The authors thought that these findings may be related to the different pathological conditions of the diseases. In the present work, miR‐29a‐3p was downregulated in LPS‐stimulated BV2 cells, and its restoration strikingly alleviated inflammatory responses and NLRP3 inflammasome by enhancing autophagy, which was similar to Shao et al's report 29 . Moreover, bioinformatics software analysis and literature showed that miR‐29a‐3p was related to CpG‐mediated DNA methylation 32 .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, miR‐29a‐3p was also reported as an autophagy regulator in various diseases. For example, miR‐29a‐3p was confirmed to inhibit macrophage polarization toward the M2 type and activate autophagy in atherosclerosis via the PI3K/AKT/mTOR pathway 29 . In contrast, miR‐29a‐3p aggravated pathological cardiac hypertrophy and ulcerative colitis by repressing autophagy 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 In addition, Beclin-1 played a key role in progression of autophagy. 29 Hence, our finding revealed that exosomal miR-133a-3p derived from BMSCs could inhibit the progression of CI/R injury via mediation of Beclin-1 and Akt/mTOR signaling.…”
Section: Discussionmentioning
confidence: 65%
“…Vascular endothelial cells are the protective barrier of vascular intima, and their damage or dysfunction can lead to an increase in intimal permeability, intimal dysfunction, and AS [ 15 ]. Although the mechanism of AS has been deeply studied, as a genetic susceptibility disease, the research on transcriptome level can fully explain the pathogenesis and provide opportunities for developing new biomarkers and treatments [ 16 ]. Thus, it is of great significance to analyze the influencing factors and pathogenesis of AS.…”
Section: Discussionmentioning
confidence: 99%